Le Sénégal Oriental à l’aube du développement minier - Isabelle Greig (EchoGéo)
Eastern Senegal is faced with the beginnings of a mining activities expansion that involves numerous and unequal players. The difficulties encountered during the survey reflect invisible stakes and palpable tensions. It’s a matter of analyzing the fragile position of local authorities in a complex set of players, facing at the same time economic globalization and unfulfilled decentralization. The region and the rural communities have a determining part to play in the direction of the territorial dynamics, between a distant national level and a too emphasized ultra-local level.